Soil CO2 evolution is driven by forage species, soil moisture, grazing pressure, poultry litter fertilization, and seasonality in silvopastures. Issue 2 (7th June 2021) - Adams, Taylor; Ashworth, Amanda J.; Sauer, Thomas
Abstract: Carbon cycling is a highly complex yet critical process, especially in silvopastures, which have multiple pools with the ability to store large amounts of C. However, it is largely unknown how site‐specific variables, including edaphic factors, vegetation type, topography, and management, affect soil CO2 flux in silvopastures. Therefore, this study aimed to evaluate CO2 fluxes in a silvopastoral system as affected by soil moisture (udic and aquic), forage species (C4 ; native grass mix and orchardgrass [C3 ; Dactylis glomerata L.]), fertilization (poultry litter and a control), and grazing pressure (grazed and ungrazed). Temperature and volumetric water content (VWC) were measured simultaneous with flux measurements during summer grazing in 2018 and 2019. Averaged across years, fluxes were at least 20% greater ( P ≤ .05) in the native mix fertilized with poultry litter than in the unfertilized native mix and fertilized or unfertilized orchardgrass, likely owing to increased microbial diversity activity in the rhizosphere of poultry litter‐amended native grass species. Across years, CO2 flux was 7% greater ( P ≤ .05) in the fertilized ungrazed areas and 7% lower ( P ≤ .05) in the unfertilized ungrazed areas, respectively, compared with both fertilized grazed and unfertilized grazed areas. Carbon dioxide flux was correlated ( P ≤ .05) with sampling date, soil temperature, and VWC. Study results improve the understanding of C dynamics in complex silvopasture systems and may assist producers in their selection of forage species and nutrient sources when designing silvopastoral systems for enhanced regional sustainability. Core Ideas: Studies of soil CO2 flux in silvopastoral systems are limited. Fluxes were greatest in a native grass mix fertilized with poultry litter. Carbon dioxide flux was correlated to sampling date, soil temperature, and soil water content.